Conchological and molecular analysis of the “nonscaly” Bornean Georissa with descriptions of three new species (Gastropoda, Neritimorpha, Hydrocenidae) - Mohd Zacaery, Khalik; Hendriks, Kasper P.; Vermeulen, Jaap J.; Schilthuizen, Menno (Pensoft Publishers, 2019)
The Bornean representatives of the genus Georissa (Hydrocenidae) have small, dextral, conical, calcareous shells consisting of ca. three teleoconch whorls. Our recent study on the Georissa of Malaysian Borneo has revealed high intra- and inter-specific variation in the “scaly” group (a group of species with striking scale-like surface sculpture). The present study on the “non-scaly” Georissa is the continuation of the species revision for the genus. The “non-scaly” species are also diverse in shell sculptures. This informal group comprises Georissa with subtle spiral and/or radial sculpture. The combination of detailed conchological assessment and molecular analyses provides clear distinctions for each of the species. Conchological, molecular, and biogeographic details are presented for 16 species of “non-scaly” Georissa. Three of these are new to science, namely Georissa corrugata sp. n., Georissa insulae sp. n., and Georissa trusmadi sp. n.